Specifičnosti uređenja glasovanja putem punomoćnika na glavnoj skupštini u hrvatskom, francuskom i slovenskom pravu - Zubović, Antonija (Podjetje in delo, 2018)
The article analyzes the issue of proxy voting at the shareholders' general meeting in Croatian, French and Slovenian law. The authors highlight the specific provisions of the legislations and point out to the open issues in its application. Although all three legal systems have harmonized their national legislation with the provisions of Shareholders' Rights Directive, there are significant differences in terms of regulating certain aspects of voting by proxy at the general meeting. These differences include conditions that must be met for appointing a proxy, form of the power of attorney, proxy solicitation and conflict of interest between the shareholder giving power of attorney and the proxy. The authors analyze the specific solutions in the adopted provisions and looks for appropriate solutions de lege ferenda.
Keywords: Direktiva o pravicah delničarjev; glasovalne pravice; institucionalni pooblaščenec; skupščina